Evaluation of the ecological and geochemical condition of geosystems of subregions of Northern Bukovyna. - KHODAN, Halyna (Iasi, 2021)
The study assessed the ecological and geochemical state of geosystems of the subregions of Northern Bukovyna: Prut-Dniester, Prut-Siret, and Bukovynian Carpathians. In the Prut-Dniester interfluve, the ecological condition of rural geosystems can be assessed as moderately favorable and low-favorable (in certain areas of the Dniester valley, where groundwater hardness exceeds standards, as well as in plakor agroecosystems, which are geochemically contaminated through the surplus of chemical fertilizers in the soil). Bukovynian Subcarpathians, in the middle part of Northern Bukovyna, are distinguished by favorable ecological conditions for both human life and rural tourism. The predominance of the leaching soil water regime of geosystems (sufficient rainfall) and notable wooded areas contributed to the sanitation of these landscapes from various artificial pollutions. In addition, there are favorable conditions for the formation of high-quality groundwater (drinking water), which should be taken into account (as an important factor) in the medical and geographical evaluation of the territory. The Carpathian subregion is the most distinct and unusual in terms of geoecological evaluation. There is a more complex set of natural conditions (vertical differentiation of landscape complexes). Fluvial terrace landscape complexes (with a chain or mosaic-scattered settlements) have highly favorable ecological and geochemical conditions. This subregion is the most optimal regarding the recreational and tourist trend. Among the geoecological factors of its development, it is worth noting the high quality of groundwater (drinking water), which, despite the excess precipitation, is sufficiently saturated with biologically essential macro- and micronutrients and have mostly medium hardness (Ca + Mg) and mineralization. All this is facilitated by water migration processes, the solubility of rock complexes, biomass decomposition, etc.
Keywords: ecological-geochemical condition; geoecological evaluation; ecological-geochemical conditions